(untitled) (Ciudades, 2017)
Methodological, instrumental and global factors seem to be decisive for the growing inability of the Spatial Planning. Furthermore, the Spatial Planning focusing on different scales and sectors is less and less able to regulate, coordinate and orient spatial development. A certain number of factors can explain that: the speculative demand of urban space, the low-cost places, the competences among municipalities or the interaction of different scalar plans. Factors, all of them, related to higher distance between plan and territory. Accordingly, it could be asserted that there is an unexpected territory as a context where the multi-sectorial, multi-scalar, multi-temporal or multi-instrumental dimensions are difficult to achieve. Through a critical revision of the factors and dimensions previously mentioned, this paper presents a conceptual renewal of the Spatial Planning based on three elements: a proactive use of the spatial information, the evaluation of planning and the use of scenarios.